(untitled) (Comparative & International Education Series, 2023)
Leaders Who Inspire: Stories of Foreign-Born University Presidents is a captivating book that introduces young readers to the remarkable stories of foreign-born college and university presidents. Through engaging narratives, readers will discover the inspiring journeys of leaders like Shirley M. Tilghman, Ángel Cabrera, A. Gabriel Esteban, and Renu Khator, who have made a significant impact on education in the United States.The book highlights the importance of diversity and inclusivity in educational institutions, showing how these leaders have transformed their campuses into welcoming spaces for students from all backgrounds. Readers will learn about the challenges these leaders faced, their unwavering determination, and their passion for empowering students to succeed. Leaders Who Inspire celebrates the power of education and the strength that comes from embracing diversity. It encourages readers to believe in themselves, pursue their dreams, and make a positive impact in their own lives and communities. About the author Krishna Bista teaches at Morgan State University in Maryland and writes about what it’s like to be a college student and how students can have exciting experiences by studying in different countries. Dr. Bista has written many books and articles about college student experiences. Order hardcopies here